A new class of genic nuclear RNA species in Arabidopsis. Issue 4 (6th February 2018) - van Wonterghem, Miranda; Thieffry, Axel; Boyd, Mette; Bornholdt, Jette; Brodersen, Peter
Abstract : Targeting of Arabidopsis PHABULOSA (PHB) mRNA by miR166 has been implicated in gene body methylation at the PHB locus. We report that the PHB locus produces an array of stable nuclear RNA species that are neither polyadenylated nor capped. Their biogenesis requires neither RNA polymerases IV/V nor miR166‐guided cleavage. The PHB RNAs are insensitive to mutation of nuclear RNA decay pathways and are conserved in several Brassicaceae species, suggesting functional relevance. Similar RNA species are also produced by another body‐methylated locus encoding the miR414 target eIF2. Our data reveal the existence of a new class of genic nuclear RNA species. Abstract :